2020
DOI: 10.1007/s40617-020-00467-2
|View full text |Cite
|
Sign up to set email alerts
|

Returning to School: Separation Problems and Anxiety in the Age of Pandemics

Abstract: The shift to the postpandemic school environment will cause dramatic changes and is likely to increase separation problems. In this article, we look at the anxiety problems that some parents and their children might experience when school reopens after the COVID-19 lockdown. Using a behavioral theory of development, we provide suggestions for how to handle the departure and separation problems that may emerge as parents drop their children off at school. Many parents are unsure about how to handle anxiety or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 5 publications
1
23
0
3
Order By: Relevance
“…Four articles provide a perspective about the relaxation of NPIs in different countries and contexts [266] , [271] , reflecting on the risks of a second wave [307] , and on the challenges children going back to school after a long period of isolation face [308] .…”
Section: Comments And/or Perspectivesmentioning
confidence: 99%
“…Four articles provide a perspective about the relaxation of NPIs in different countries and contexts [266] , [271] , reflecting on the risks of a second wave [307] , and on the challenges children going back to school after a long period of isolation face [308] .…”
Section: Comments And/or Perspectivesmentioning
confidence: 99%
“…Third-grade junior high school students in Huanggang first returned to school on May 26, which means school-aged children were still at home during the study period (25). Possible reasons for concerns about resuming work could have been separation anxiety and the stress created by the lack of time to secure childcare or education (26,27). Demographic risk factors suggested greater understanding and support for female staff, especially those who were pregnant or preparing for pregnancy and those who had school-age children in their families.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, other studies have shown that teachers who teach face-to-face are about roughly twice infection risk of those who teach online. This will increase the risk of infection in the family 27,28 . These reasons may lead to big pressure on teachers in the return-to-school.…”
Section: Discussionmentioning
confidence: 99%